(3cJGFH CYdGe GdCNHGQ ef abgGA ePgH GdfYeGf GdeNJGQs - (3Gdcahj , eMehO Hf SdjeGf GdMfaj GdQhej,J (B990 (3g` s ((3eMeO Hf ceGd GdCfUGQi s)
(3ChdgG (B:s
(3ChdI JQLeI aNQ GdOjf bGVjNGf CHj Ydi GdMSf Hf efUhQ GdaQZGfi s
(3BNQgG (B:s
(3Efc hdi GdELGHI SejY GdOYGA , jG QH KHJ bOei hbdHi SHMGfc Gddge CfJ MSHj s
(3GdfUa GdKGfj ef fSNI KGdKIs
(3fbdgG GdfGSN Yf fSNI cJHgG CMO JdGejP GdeDda Sf``(B987(3``I g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B168s
Keywords: (3GdJGQjNs